RELEVANSI SOSIOLOGI DAN ANTROPOLOGI DALAM PENDEKATAN STUDI ISLAM: PERSPEKTIF BARU UNTUK PEMAHAMAN YANG LEBIH MENDALAM - Fikar, M; Julhadi; Kamal, Tamrin; Hakim, Rosniati; Hanafi, Abdul Halim (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Islamic studies has long been a rich and diverse field of study, encompassing a wide range of disciplines including theology, law, history, and philology. However, sociological and anthropological approaches offer new perspectives that can enrich our understanding of Islam and Muslim societies. This research aims to explore the relevance and contribution of sociology and anthropology in Islamic studies. By utilizing qualitative methods, including literature analysis and in-depth interviews with experts, this research examines how these approaches can provide deeper insights into religious practices, cultural identities, and social dynamics within Muslim communities. Research findings show that sociology helps in understanding social structures and power relationships in Muslim communities, while anthropology provides tools for exploring symbolic meanings and performing ritual practices. The combination of these two approaches opens up opportunities for a more holistic and interdisciplinary study of Islam, which does not only focus on texts and doctrines, but also on the life experiences and daily practices of Muslims. This research concludes that the integration of sociology and anthropology in Islamic studies is very relevant and important to produce a more comprehensive and contextual understanding of Islam in the contemporary world.Keywords: Islamic Studies; Sociology; Anthropology; Interdisciplinary Approach.